Irinotecan dose reduction in metastatic colorectal cancer patients with homozygous UGT1A1*28 polymorphism: a single-center case series. Issue 7 (July 2022) - Tsai, Hsiang-Lin; Chen, Po-Jung; Chen, Yen-Cheng; Li, Ching-Chun; Chang, Tsung-Kun; Su, Wei-Chih; Yin, Tzu-Chieh; Huang, Ching-Wen; Wang, Jaw-Yuan
Objective: The UGT1A1*28 polymorphism reduces UGT1A1 enzymatic activity, which may increase the risk of severe toxicity in patients who receive standard-dose irinotecan, such as severe neutropenia and diarrhea. This real-world study assessed the optimal irinotecan dose in terms of efficacy and toxicity in metastatic colorectal cancer (mCRC) patients homozygous for the UGT1A1*28 polymorphism and receiving FOLFIRI plus bevacizumab or cetuximab as first-line therapy. Methods: We analyzed toxicity and treatment outcomes in seven mCRC patients who were homozygous for UGT1A1*28 and received FOLFIRI plus bevacizumab or cetuximab, with an initial irinotecan dose of 120 mg/m 2 . Results: Six of the seven patients tolerated 120 mg/m 2 irinotecan without requiring dose reductions in subsequent cycles. The overall response and disease control rates were 43.0% (3/7) and 71.4% (5/7), respectively. The median progression-free survival and overall survival were 11.0 and 33.0 months, respectively. Only one severe adverse event, grade III neutropenia (2.5%), was observed. Conclusions: mCRC patients homozygous for the UGT1A1*28 allele can tolerate irinotecan at an initial dose of 120 mg/m 2 with favorable oncological outcomes and toxicity profiles. Further prospective studies are warranted to optimize irinotecan-based chemotherapy in these patients.